2018
DOI: 10.1016/j.neuropharm.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine modulates contextual fear extinction through changes in ventral hippocampal GABAergic function

Abstract: Numerous studies have attributed the psychopathology of anxiety and stress disorders to maladaptive behavioral responses such as an inability to extinguish fear. Therefore, understanding neural substrates of fear extinction is imperative for developing more effective therapies for anxiety and stress disorders. Although several studies indicated a role for cholinergic transmission and nicotinic acetylcholine receptors (nAChRs) in anxiety and stress disorder symptomatology, very little is known about the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Furthermore, we measured an increase in mRNA for the CREB‐binding protein, an epigenetic regulator of transcription that is involved in various neuronal functions (Barrett et al, 2011; Valor et al, 2011) and whose deletion has shown to promote resilience (Manners et al, 2019) and neurogenesis in the hippocampus (Gundersen et al, 2013). Moreover, we observed increased levels in the PFC of R− mice of mRNA for the enzyme responsible for synthetizing GABA, glutamic acid decarboxylase 2 (GAD2), whose function is essential for proper neuronal communication and correct fear coping (Kutlu et al, 2018). Interestingly, mice lacking GAD2 (GAD2 −/− ) have shown increased susceptibility to stress (Qi et al, 2018), whereas heterozygous mice (GAD2 +/− ) showed increased resilience (Müller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we measured an increase in mRNA for the CREB‐binding protein, an epigenetic regulator of transcription that is involved in various neuronal functions (Barrett et al, 2011; Valor et al, 2011) and whose deletion has shown to promote resilience (Manners et al, 2019) and neurogenesis in the hippocampus (Gundersen et al, 2013). Moreover, we observed increased levels in the PFC of R− mice of mRNA for the enzyme responsible for synthetizing GABA, glutamic acid decarboxylase 2 (GAD2), whose function is essential for proper neuronal communication and correct fear coping (Kutlu et al, 2018). Interestingly, mice lacking GAD2 (GAD2 −/− ) have shown increased susceptibility to stress (Qi et al, 2018), whereas heterozygous mice (GAD2 +/− ) showed increased resilience (Müller et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A literature survey indicates that NMDA antagonists demonstrate a decreasing effect on the acquisition of nicotine-induced CPP (Li et al, 2014;Yararbas et al, 2010). It was also indicated in a previous study that GABA receptor agonists, PPAR agonists and calcium channel blockers attenuate the reinstatement of nicotine-induced CPP (Aguilar, Rodríguez-Arias, Miñarro, 2009;Biala, Budzynska, 2008;Blanco-Gandía et al, 2018;Fattore et al, 2009;Jackson et al, 2017;Kutlu et al, 2018;Le Foll et al, 2013;Matheson, Le Foll, 2020;Panlilio, Justinova, Goldberg, 2013). Moreover, previous research illustrated that resveratrol diminishes morphine-induced CPP, morphine dependence, and methamphetamine-induced hyperactivity and dopamine overflow in rodents (Han et al, 2014;Miller et al, 2013;Rezaee et al, 2020).…”
Section: Resveratrol Inhibits Nicotine-induced Conditioned Place Pref...mentioning
confidence: 86%
“…Nicotine changes GABA activity in the brain by various mechanisms (D 'Souza, 2016). It was also found that GABA agonists decrease nicotine dependence, and reinstatement, and also accelerate the extinction of nicotine-conditioned place preference (Biala, Budzynska, 2008;Fattore et al, 2009;Kutlu et al, 2018;Li et al, 2012;Paterson, Froestl, Markou, 2004;Varani et al, 2014). Furthermore, a series of recent studies show that resveratrol stimulates GABA.…”
Section: Discussionmentioning
confidence: 97%
“…Prior preclinical studies have shown that nicotine may interfere with fear extinction (an important part of PTSD). 67 These effects may explain the observation of higher mGluR5 availability in smoking associated with PTSD.…”
Section: Discussionmentioning
confidence: 99%